ON CHINESE EDUCATION IN THAILAND IN CONTEXT OF “ONE BELT AND ONE ROAD”: Some Problems and Preliminary Solutions - CHEN, KAI (Chinese Language and Culture Journal, 2019)
Chinese education is one of the most important carriers of China’s traditional culture.This article explores the dynamics of the Chinese education in Thailand, as well as someofthe problemsfacing the Chinese education in this country, in the context of “One Belt and One Road”. Then, it discusses the preliminarysolutions to the above-mentioned challenges.